Uncovering the effect of waterlogging stress on plant microbiome and disease development: current knowledge and future perspectives - Tyagi, Anshika; Ali, Sajad; Mir, Rakeeb Ahmad; Sharma, Sandhya; Arpita, Kumari; Almalki, Mohammed A.; Mir, Zahoor Ahmad (Frontiers in Plant Science, 2024)
Waterlogging is a constant threat to crop productivity and ecological biodiversity. Plants face multiple challenges during waterlogging stress like metabolic reprograming, hypoxia, nutritional depletion, reduction in gaseous exchange, pH modifications, microbiome alterations and disease promotion all of which threaten plants survival. Due to global warming and climatic change, the occurrence, frequency and severity of waterlogging has dramatically increased posing a severe threat to food security.Thus, developing innovative crop management technologies is critical for ensuring food security under changing climatic conditions. At present, the top priority among scientists is to find nature-based solutions to tackle abiotic or biotic stressors in sustainable agriculture in order to reduce climate change hazards. In this regard, utilizing plant beneficial microbiome is one of the important natures based remedial tool for mitigating abiotic stressors like waterlogging stress. Beneficial microbiota provides plants multifaceted benefits which improves their growth and stress resilience. Plants recruit unique microbial communities to shield themselves against the deleterious effects of biotic and abiotic stress. In comparison to other stressors, there has been limited studies on how waterlogging stress affects plant microbiome structure. Therefore, it is important to understand and explore how waterlogging induced plant microbiome alterations and how these changes affect plant survival. Here, we discussed the effect of waterlogging stress in plants and its microbiome. We also highlighted how waterlogging stress promotes pathogen occurrence and disease development in plants. Finally, we highlighted some key points that warrants future investigation to decipher the molecular complexity of waterlogging stress induced changes in plant microbiome.